1996
DOI: 10.1159/000217980
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Bound (MUC1) and Secretory (MUC2, MUC3, and MUC4) Mucin Gene Expression in Human Lung Cancer

Abstract: Abnormalities of mucin-type glycoproteins have been described in lung cancers, but their molecular basis is unknown. In this study, mucin-core-peptide-specific antibodies and cDNA probes were used to determine the relative expression of mucin genes corresponding to one membrane-bound mucin (MUC1), two intestinal mucins (MUC2 and MUC3), and one tracheobronchial mucin (MUC4) in normal (nonneoplastic) lung, and in lung neoplasms. Normal lung tissues exhibited a distinct pattern of mucin gene expression, with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 23 publications
7
53
1
1
Order By: Relevance
“…Some previous studies have reported that MUC4 may have a prognostic value in cancer including breast cancer. 28,29 However, we did not find any associations between MUC4 and any of the clinicopathological parameters or patients outcome in our series. The functions that have previously been suggested as possible tumour precipitating factors 39,40 have not been studied individually in this study, and more work still needs to be carried out to determine the role of this mucin in breast cancer.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Some previous studies have reported that MUC4 may have a prognostic value in cancer including breast cancer. 28,29 However, we did not find any associations between MUC4 and any of the clinicopathological parameters or patients outcome in our series. The functions that have previously been suggested as possible tumour precipitating factors 39,40 have not been studied individually in this study, and more work still needs to be carried out to determine the role of this mucin in breast cancer.…”
Section: Discussioncontrasting
confidence: 79%
“…28 The deregulation of MUC4 may be a factor for tumour progression and its altered expression has been found in a number of carcinomas. 29,30 In this study, we have assessed the expression profiles of different mucins and evaluate their prognostic significance in a large and well-characterized series of breast cancer, prepared as tissue microarrays (TMA), using immunohistochemistry.…”
mentioning
confidence: 99%
“…34 MUC4 mRNA expression has also been described in lung carcinomas by Northern blot analysis and RT-PCR. [37][38][39] In this study, we confirmed the frequent expression of both MUC4 protein and transcripts in lung adenocarcinomas.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, in recent studies, a progressive increase in MUC4 expression has been observed in pancreatic intraepithelial neoplastic lesions (11,12), indicating its role in disease development. The up-regulation of MUC4 in several other human adenocarcinomas (13)(14)(15)(16) also indicates the potential importance of this mucin in tumor biology.…”
Section: Introductionmentioning
confidence: 97%